El reino visigodo de Toledo y los matrimonios mixtos entre godos y romanos - Valverde, Mª Rosa (Gerión. Revista de Historia Antigua, 2002)
The LV 3.1.1, issued during the kingship of Leovigild, revoked a previous law banning the marriages between Goths and Romans. In all the civil laws which preceded and followed the LV 3.1.1. and that prohibited the mixed unions between people of different religions and/or origins, we discover a political and religious ground. Through the insertion of this derogatory law in its historic context, we try to make evident that Leovigild’s disposition would have had the same kind of political and religious motivations as the other legislative measures that had banned the mixed marriages.